2017
DOI: 10.26858/eltww.v4i2.4498
|View full text |Cite
|
Sign up to set email alerts
|

Lecturer’s Competence and Students’ Writing Proficiency at University Level in Indonesia

Abstract: This research explored the influence of lecturer’s competences toward students’ writing proficiency at the English Education Study Program of Dayanu Ikhsanuddin University, Indonesia. The research question that was raised up of this research was do the lecturer competence influence students’ writing proficiency? This research aimed to investigate the influence of lecturer competence toward students’ writing proficiency. This research employed ex post facto method. The population was the fourth semester student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Apart from that, writing is a difficult procedure that requires planning, composition, rewriting and modification (Vijayavalsalan, 2016). In line with these, some studies found out that students' results in writing test were not satisfactory (Persadha (2016), Arisman et al (2017)). A similar indication was also shown by 51 respondents in my preliminary observations that they encountered difficulties in writing, even in composing a single paragraph.…”
Section: Introductionmentioning
confidence: 98%
“…Apart from that, writing is a difficult procedure that requires planning, composition, rewriting and modification (Vijayavalsalan, 2016). In line with these, some studies found out that students' results in writing test were not satisfactory (Persadha (2016), Arisman et al (2017)). A similar indication was also shown by 51 respondents in my preliminary observations that they encountered difficulties in writing, even in composing a single paragraph.…”
Section: Introductionmentioning
confidence: 98%
“…It contributes as well as an essential meaning to comprehend the foreign language (Nuratika, Yanti, & Mayer, 2019). In academia, vocabulary has a big part in supporting everyone to communicate with other people and comprehend meaning in the written word (Arisman, Hamra, & Weda, 2017). Furthermore, we still convey our expression without grammar but without vocabulary, there is little that can be conveyed (Alhamdi, Salih, & Abd, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The success of the learning process depends on the ability of a lecturer to manage his/ her learning. By mastering all the competencies, a lecturer can create an enjoyable and pleasant learning environment [1], [2].…”
Section: Introductionmentioning
confidence: 99%